2023
DOI: 10.3390/app13148209
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Fake News in Arabic Tweets Using Deep Learning

Shatha Alyoubi,
Manal Kalkatawi,
Felwa Abukhodair

Abstract: Fake news has been around for a long time, but the rise of social networking applications over recent years has rapidly increased the growth of fake news among individuals. The absence of adequate procedures to combat fake news has aggravated the problem. Consequently, fake news negatively impacts various aspects of life (economical, social, and political). Many individuals rely on Twitter as a news source, especially in the Arab region. Mostly, individuals are reading and sharing regardless of the truth behin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Although the BiLSTM model achieved good results, with precision, recall, and F1-score of 92%, 93%, and 93%, respectively, its performance was lower than that of the Att-BiLSTM model, thus proving the efficacy of the attention mechanism in enhancing the overall model performance. To evaluate the performance of our model, we compared the performance of our proposed model with the baseline models in studies [10,11,12,14] which utilized the same dataset. We compared our model with baseline models in four studies from the related works section that utilized the AraNews dataset and the ArCOV19-Rumors dataset, including:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the BiLSTM model achieved good results, with precision, recall, and F1-score of 92%, 93%, and 93%, respectively, its performance was lower than that of the Att-BiLSTM model, thus proving the efficacy of the attention mechanism in enhancing the overall model performance. To evaluate the performance of our model, we compared the performance of our proposed model with the baseline models in studies [10,11,12,14] which utilized the same dataset. We compared our model with baseline models in four studies from the related works section that utilized the AraNews dataset and the ArCOV19-Rumors dataset, including:…”
Section: Resultsmentioning
confidence: 99%
“…In [14], the authors introduce deep learning-based models for identifying fake news within Arabic tweets by exploiting the content of the news in tweets. They conducted experiments using CNN and BiLSTM architecture and investigated the utilization of five distinct word embeddings, including word2vec, FastText, and a BERT-based model for extracting textual features.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, RF outperformed the others using 4-and 5-grams based on accuracy. In study [69], they also relied on a set of extracted features from user and textual features. To extract the textual features, they used both classic word embedding (word2vec, fastText, and Keras embedding layer) and context-based embedding (Multilingual Arabic Bidirectional Encoder Representations from Transformers (MARBERT) and ARBERT) with deep learning models [70].…”
Section: Fake Nwes Detection and Arabic Languagementioning
confidence: 99%
“…The study found that the BiLSTM model was the most accurate compared to other employed models. Alyoubi et al [26] applied deep learning techniques to identify fake news within Arabic tweets. Their model took into account both the content of the news and the social background of the users spreading the news.…”
Section: Related Workmentioning
confidence: 99%
“…Technique Accuracy [17] QARiB transformer 95% [18] CNN 95% [19] LR using n-gram-level TF-IDF 93% [21] RF 78% [22] CNN-LSTM 91% [23] AFND-CNN-LSTM 70% [24] ARBERT 98% [25] BiLSTM 84% [26] CNN using MARBERT embedding model. 95% Proposed Stacking Classifier (bagging, boosting, baseline) 99%…”
Section: F Performance Comparison With Existing Modelsmentioning
confidence: 99%